The Product Life Cycle Theory: Empirical Evidence - Mullor-sebastián, Alicia (Journal of International Business Studies, 1983)
This paper presents 3 empirical tests of the product life cycle theory based on U.S. trade data and on a relatively new data series providing information about a larger number of products and at a lower level of aggregation than the data used previously. The results of the tests strongly support the hypothesis that industrial product groups behave in the manner predicted by the product life cycle theory on world markets. In the case of individual products, however, the results provide less support for the theory. The policy implication is that development strategies should rely on industrial sectors rather than on individual commodities.